PENGARUH ORIENTASI PASAR PADA KUALITAS LAYANAN, KEPUASAN PELANGGAN, DAN LOYALITAS PELANGGAN SPEEDY PT TELKOM DI KOTA YOGYAKARTA - Abdillah, Ihsany; Adhilla, Fitroh (Jurnal Fokus Manajemen Bisnis, 2014)
Market orientation is believed to be a source of competitive advantage that is difficult to imitate by competitors. This study aimed to determine the effect of market orientation on service quality, customer satisfaction, and customer loyalty Speedy PT Telkom in the city of Yogyakarta. The population in this study are all PT Telkom Speedy customers who live in city of Yogyakarta. Data analysis methods used in this study include descriptive and inferential methods, inferential method used is path analysis. The results of goodness of fit model shows that the X2 value, the value of CFI, and RMSEA values have had a good match. Based on the analysis of data shows that the determinants of customer loyalty Telkom Speedy Yogyakarta is a market orientation quality of service, and customer satisfaction.